Anti–IL-4R versus anti–IL-5/5R after anti–IL-5/5R failure in asthma: An emulated target trial - Bonniaud, Philippe; Beurnier, Antoine; Boudjemaa, Amel; Bourdin, Arnaud; Maurer, C.; Beurnier, A.; Roux, P.; Margelidon, V.; Boudjemaa, A.; Mangiapan, G.; Freymond, N.; Russier, M.; et al. (Journal of allergy and clinical immunology, 2024)
[Display omitted] Switching biologics is now common practice in severe eosinophilic asthma. After insufficient response to anti–IL-5 or 5 receptor (anti–IL-5/5R), the optimal switch between an anti–IL-4R mAb (interclass) or another anti–IL-5/5R drug (intraclass) remains unknown. We sought to compare the effectiveness of these 2 strategies in asthma control in patients with severe eosinophilic asthma and insufficient response to an anti–IL-5/5R mAb. We emulated a target randomized trial using observational data from the Recherche sur les AsthMes SEvèreS (RAMSES) cohort. Eligible patients were switched to an anti–IL-4R mAb or another anti–IL-5/5R drug after insufficient response to an anti–IL-5/5R mAb. The primary outcome was the change in Asthma Control Test score at 6 months. Among the 2046 patients in the cohort, 151 were included in the study: 103 switched to an anti–IL-4R mAb and 48 to another anti–IL-5/5R. At 6 months, the difference in Asthma Control Test score improvement was not statistically significant (mean difference groups, 0.82 [−0.47 to 2.10], P = .213). The interclass group exhibited greater cumulative reduction in oral corticosteroid dose (Pinter-intra, −1.05 g [−1.76 to −0.34], P = .041). The interclass group had a better effect, although not significantly, on reducing exacerbations (Δinter-intra, −0.37 [−0.77 to 0.02], P = .124) and increasing lung function (FEV1) (126.8 mL [−12.7 to 266.4], P = .124). After anti–IL-5/5R mAb insufficient response, switching to dupilumab demonstrated similar improvement in Asthma Control Test scores compared with intraclass switching. However, it appeared more effective in reducing oral corticosteroid use. Larger studies are warranted to confirm these results.